2016
DOI: 10.1016/j.tjog.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the laparoscopic versus conventional open method for surgical staging of endometrial carcinoma

Abstract: Our preliminary results showed that the laparoscopic method for staging endometrial cancer was technically feasible and efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
5
13
1
Order By: Relevance
“…Most of the studies reported lower blood loss in the laparoscopy group (9,(12)(13)(14). In our study, the difference between pre-operative and post-operative hemoglobin values was higher in the laparotomy group and was similar to published data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most of the studies reported lower blood loss in the laparoscopy group (9,(12)(13)(14). In our study, the difference between pre-operative and post-operative hemoglobin values was higher in the laparotomy group and was similar to published data.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the previous studies reported significantly shorter hospital stays with laparoscopy (9,13,24). We found that both groups were similar in terms of hospitalization.…”
Section: Discussionsupporting
confidence: 65%
“… 4 5 The survival outcome of cancer patients obtained through laparoscopy is not inferior to that obtained through laparotomy. 6 7 To provide an international standard of surgical care for female cancers, the gynecologic cancer team of Tzu Chi General Hospital initiated laparoscopic staging surgery in 2010 and laparoscopic radical hysterectomy in 2011. Since then, the proportion of laparoscopic gynecologic cancer surgery rapidly increased annually and reached 100% in 2016.…”
Section: Silent Mentor Program Improves Our Surgical Level and Patienmentioning
confidence: 99%
“…Previous research comparing the OS with the LS [6] and the LS with the RS exists [7], along with one meta-analysis comparing all three approaches [8]. However, data are scarce concerning the direct comparison of survival outcomes among the OS, the LS, and the RS for endometrial cancer [9].…”
Section: Introductionmentioning
confidence: 99%